Female sex workers incarcerated in New York City jails: prevalence of sexually transmitted infections and associated risk behaviors. Issue 4 (17th May 2013) - Parvez, Farah; Katyal, Monica; Alper, Howard; Leibowitz, Ruth; Venters, Homer
Abstract : Objectives: Sexually transmitted infections (STIs) are an important cause of morbidity among incarcerated women and female sex workers (FSW). Little is known about FSW incarcerated in New York City (NYC) jails. We reviewed jail health records to identify the STI and HIV prevalence among newly incarcerated FSW in NYC jails. We also examined the relationship of demographics and self-reported clinical and risk behaviour history with FSW status and compared FSW with non-FSW incarcerated women to identify FSW predictors and, guide NYC jail programme planning and policy. Methods: We retrospectively reviewed routinely collected jail health record data to identify the prevalence of chlamydia (Ct), gonorrhoea (Ng) and HIV infection among women newly incarcerated in NYC jails in 2009–2010 (study period) and studied the relationship of STIs, demographics and self-reported clinical and risk behaviour history with FSW status. Results: During the study period, 10 828 women were newly incarcerated in NYC jails. Of these, 10 115 (93%) women were tested for Ct and Ng; positivity was 6.2% (95% CI 5.7% to 6.7%) and 1.7% (95% CI 1.4% to 1.9%), respectively. Nine percent had HIV infection. Seven hundred (6.5%) were defined as FSW. FSW were more likely to have Ct (adjusted OR (AOR): 1.55; 95% CI 1.17 to 2.05; p<0.0001) but not Ng or HIV. FSW were more likely to report age 20–24 years, reside in boroughs other than Manhattan, ≥6 prior incarcerations, ≥2 incarcerations during the study period, condom use with current sex partners, multiple sex partners and current drug use. Conclusions: Women incarcerated in NYC jails had high rates of Ct, Ng, and HIV infection. FSW were at higher risk for Ct than non-FSW incarcerated women. These findings are being used to design targeted interventions to identify FSW, provide clinical and preventive services in jail and coordinate care with community partners.